HR LEADERS: BUILDING EMOTIONAL RESILIENCE AMIDST COVID19 AT WORKPLACE - Dr. Ankita Saxena (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
With the current unprecedented pandemic situation, conventional methods of working have become relics of past times. It is critical for HR to implement modern approaches and cycles as per the new typical. Remote working has made the things more mechanised and has demolished the demarcation between personal and professional life. 24*7 working hours, zoom fatigue, lot of uncertainties related to health, job etc. are adversely affecting the emotional and psychological wellness of employees at workplace. In such times it is a great challenge for HR leaders to keep the workforce motivated, enthusiastic and involved. The current conceptual paper throws some light over the areas which were devastated by COVID19 and how the employees at workplace are affected mentally and emotionally by the current pandemic situation. Finally suggesting the role of HR leaders in overcoming the above problem by taking certain steps like conducting counselling sessions for employees, arranging informal meetings with HR professionals and conducting various mentorship and skill development programs to achieve employee involvement. Each business must comprehend that they have obligation towards their employees & laying-off is not a solution.